O impacto do simples federal no nível de emprego da indústria brasileira - Carlos Henrique L. Corseuil; Rodrigo Leandro Moura (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper aims to evaluate the impact of a tax incentive program targeted to small business (SIMPLES) on employment growth. The evaluation is conducted for two distinct periods, namely 1997 when the program was first implemented and 1999 when the eligibility rule was modified in order to accomplish a broader eligible group of firms. The evaluation takes into account two distinct channels through which the effects may operate. The first is the employment variation in firms that became eligible, while the second is the change in the survival probability experienced by the same group of firms. Moreover, each of these channels can be activated either by the tax reduction dimension of the program or the red tape simplification dimension. Our results points to positive effects on employment growth only for the red tape simplification dimension in the 1997 sample.
Keywords: J21; H25; 330; Fertigungsberufe; KMU; Steuervergünstigung; Brasilien